Size-Dependent Chlorinated Nitrogen-Doped Carbon Nanotubes: Their Use as Electrochemical Detectors for Catechol and Resorcinol - Winny Kgabo Maboya; Mologadi Nkiyasi Rantho (International Journal of Electrochemistry)
In this study, various-sized nitrogen-doped carbon nanotubes (NCNTs) were fabricated by varying the concentration of chlorine in the feed. The diameter of the NCNTs was found to influence the sensing ability of the nanomaterials when coated onto the glassy carbon electrode (GCE) and used for the detection of catechol (CC) and resorcinol (RS). Larger diameter NCNTs (denoted NCNTs (2 : 1)) were produced when a low concentration of chlorine was added into the acetonitrile feed, whereas smaller diameter NCNTs (denoted NCNTs (1 : 2)) were produced when a large concentration of chlorine was added. This investigation revealed that the addition of controllable amounts of chlorine during the fabrication of NCNTs led to the creation of nanostructures with different properties. The greatest current response which was evidenced by an enhanced anodic peak of CC and RS was obtained when GCE was coated with NCNTs (2 : 1), and this was attributed to their large diameter and high graphitic nature which facilitated electron transfer as evidenced by scanning electron microscopy (SEM), Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS) analysis. A linear response was obtained when varying the concentration of both CC and RS, with the limits of detection of about 0.059 μM (CC) and 0.034 μM (RS) (3S/M) obtained.